2022
DOI: 10.31603/ae.7248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hexane Addition in Waste Plastic Fuel-Biodiesel-Diesel Blends on the Performance and Emission Characteristics of DI Diesel Engine

Abstract: The current study's sole objective is to evaluate the impact of hexane's addition to blends of diesel, waste plastic fuel, and jatropha biodiesel. Five fuel samples have been made in order to do this, including diesel-waste plastic fuel-jatropha biodiesel (D70WPF20JB10 and D70WPF10JB20), diesel-hexane-waste plastic fuel-jatropha biodiesel (D65HX5WPF20JB10 and D65HX5WPF10JB20), and plain diesel (D100) as a reference fuel. Following thorough characterization, studies using spectroscopic techniques such as FTIR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Potential additives to improve blend properties over pure canola oil include n-hexane [18]. An example of a paper confirming the beneficial properties of n-hexane and fuel blends with waste plastic fuel and jatropha biodiesel and diesel fuel is [19]. The results presented there confirm that the addition of n-hexane can improve the physicochemical properties of the fuel and enable the reduction in CO and NO X in the engine exhaust.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Potential additives to improve blend properties over pure canola oil include n-hexane [18]. An example of a paper confirming the beneficial properties of n-hexane and fuel blends with waste plastic fuel and jatropha biodiesel and diesel fuel is [19]. The results presented there confirm that the addition of n-hexane can improve the physicochemical properties of the fuel and enable the reduction in CO and NO X in the engine exhaust.…”
Section: Introductionmentioning
confidence: 67%
“…The results presented there confirm that the addition of n-hexane can improve the physicochemical properties of the fuel and enable the reduction in CO and NO X in the engine exhaust. Additionally, engine research reveals that the fuel samples with n-hexane added have improved thermal and volumetric efficiencies and lower BSFC (brake specific fuel consumption) [19].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that NOx, HC, CO, BSFC values decreased, while exhaust gas temperature (EGT) and CO2 values increased. Kumar et al [5] experimented the influences of blending WPF and jatropha biodiesel with diesel in view of emissions and performance. The results of adding hexane to these mixtures have also been examined.…”
Section: Introductionmentioning
confidence: 99%